Die manifestering van Septuaginta-invloed in die Sondergut-Lukas - Steyn, Gert J. (Hervormde teologiese studies, 1989)
The manifestation of Septuagint-influence in the Sondergut-Lukas It has often been postulated that the Gospel of Luke was influenced by the Septuagint. In a recent study this was proven to be true when research on the language and style of the Gospel was conducted. It manifested a number of similarities between the Septuagint and the Gospel - especially within the source-material peculiar to Luke (Sondergut-Lukas). The childless-motif in Luke 1 and the last part of Jesus’ genealogy in Luke 3 are representative examples of this.